Antimycobacterial 2-aminoquinazolinones and benzoxazole-based oximes: synthesis, biological evaluation, physicochemical profiling and supramolecular derivatization - Njaria, Paul Magutu (Department of Chemistry, 2018)
Tuberculosis (TB) is a life-threatening infectious disease caused by Mycobacterium tuberculosis (Mtb). Globally, TB is a major public health burden with an estimated 10.4 million new cases and 1.8 million deaths reported in 2015. Although TB is curable, the treatment options currently available are beset by numerous shortcomings such as lengthy and complex treatment regimens, drug-drug interactions, drug toxicities, as well as emergence of widespread multi-drug resistance. Therefore, there is an urgent and compelling need to develop new, more effective, safer drugs with novel mechanisms of action, and which are capable of shortening treatment duration. This study focused on hit-to-lead optimization of two new classes of compounds with potential anti-TB properties: 2-aminoquinazolinones (AQZs) and benzoxazole-based oximes (BZOs). A hit compound for each of these classes with low micromolar antimycobacterial activity had previously been identified through phenotypic whole-cell in vitro screening.